Multiple regulatory genes control expression of a gene family during development of Dictyostelium discoideum. - Alexander, S (1986)
Mutant strains of Dictyostelium discoideum carrying dis mutations fail to transcribe specifically the family of developmentally regulated discoidin lectin genes during morphogenesis. The phenotypes of these mutants strongly suggested that the mutations reside in regulatory genes. Using these mutant strains, we showed that multiple regulatory genes are required for the expression of the lectin structural genes and that these regulatory genes (the dis+ alleles) act in trans to regulate this gene family. These regulatory genes fall into two complementation groups (disA and disB) and map to linkage groups II and III, respectively. A further regulatory locus was defined by the identification of an unlinked supressor gene, drsA (discoidin restoring), which is epistatic to disB, but not disA, and results in the restoration of lectin expression in cells carrying the disB mutation. Mutant cells carrying the drsA allele express the discoidin lectin gene family during growth and development, in contrast to wild-type cells which express it only during development. Therefore, the suppressor activity of the drsA allele appears to function by making the expression of the discoidin lectins constitutive and no longer strictly developmentally regulated. The data indicate that normal expression of the discoidin lectins is dependent on the sequential action of the disB+, drsA+, and disA+ gene products. Thus, we described an interacting network of regulatory genes which in turn controls the developmental expression of a family of genes during the morphogenesis of D. discoideum.